HOX Gene Aberrant Expression in Skin Melanoma: A Review - Gérald E. Piérard; Claudine Piérard-Franchimont (Journal of Skin Cancer)
The homeobox family and its subset of HOX gene products represent a family of transcription factors directing DNA-protein and protein-protein interactions. In the embryo, they are central regulators in cell differentiation during morphogenesis. A series of genes of the four HOX gene clusters A, B, C, and D were reported to show aberrant expressions in oncogenesis, particularly in cutaneous malignant melanoma (CMM). They are involved in cell proliferation and progression in the CMM metastatic path. We present relevant peer-reviewed literature findings about the aberrant expression of HOX genes in CMM. The number of CMM cell nuclei exhibiting aberrant HOX protein expression appears correlated with tumour progression.